The Effect of Chitosan-Gelfoam Cacao Pod Husk on Wound Epithelial Thickness in the Post-Extraction Tooth with Anticoagulant Therapy - Astika Swastirani; Fiorina Divasinta Mirelia Marsudi (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2022)
Tooth extraction is removing a tooth from its socket when it cannot be restored. Tooth extraction performed in patients on anticoagulant therapy can increase the risk of excessive bleeding. Therefore, a local hemostatic agent is needed to accelerate the hemostasis process and reduce the risk of tooth extraction complications in anticoagulant users. This study aims to determine the effect of chitosan-gelfoam extract of cacao pod husk to increase epithelial thickness in the post-extraction socket of male Wistar rats with anticoagulant therapy. This research used quantitative data collection techniques on 24 male Wistar rats who were given anticoagulant therapy. It was divided into eight groups: negative control group H+3, negative control group H+7, positive control with oral tranexamic acid therapy H+3, positive control with oral tranexamic acid therapy H+7, treatment 1 with 1 ml chitosan-gelfoam cacao pod husk extract therapy H+3, treatment 1 with 1 ml chitosan-gelfoam cacao pod husk H+7, treatment 2 with 10 ml chitosan-gelfoam cacao pod husk H+3, and treatment 2 with 10 ml chitosan-gelfoam cacao pod husk H+7. The test animals were decapitated on the 3rd and 7th day. The histology preparations, observations, and statistical tests were then carried out. The statistical tests showed that chitosan gelfoam extract of cacao pod husk with doses of 1.6% and 15% extract of cacao pod husk was able to replace the effectiveness of tranexamic acid. The 15% dose had better significance than the 1.6% dose. This research is expected to contribute to the farmers’ welfare and the cacao industry by converting cacao pod waste into helpful medicine.